Hidden forces: the impact of cancer-associated fibroblasts on non-small cell lung cancer development and therapy - Ziheng Wu; Meilin Luo; Huiyi Hu; Zhijun Jiang; Yinan Lu; Zhi-Jie Xiao (Journal of Translational Medicine)
Abstract Non-small cell lung cancer (NSCLC) continues to be a leading cause of cancer-related deaths globally, primarily due to its late diagnosis and the complex nature of its tumor microenvironment (TME). Within this environment, cancer-associated fibroblasts (CAFs) play a crucial role in regulating NSCLC progression and therapeutic resistance. Recent advancements in single-cell and spatial technologies have uncovered significant heterogeneity among CAFs, revealing distinct subpopulations with varying cellular origins, phenotypes, and functions. Besides, the role of small extracellular vesicles (sEVs) in facilitating bidirectional communication highlights functional importance of CAF derived sEVs in mediating the crosstalk between cancer and TME, implicating the potential of CAF-sEVs to be un-invasive diagnostic biomarkers for NSCLC. Despite such new insights, challenges remain exist, particularly concerning the mechanisms that drive CAF plasticity, the interactions between specific CAF subsets with cancer cells or immune cells, and the translational significance of CAF-sEVs. In this review, we summarize the latest advances in our understanding of CAF heterogeneity, the functional roles and clinical relevance of CAFs and their secreted sEVs in driving NSCLC, and the translational landscape of CAF-targeted strategies. By critically evaluating the most recent evidence, this review provides clinically relevant insights and highlights future directions for overcoming CAF-mediated barriers to therapy. Our aim is to facilitate the development of more precise, biomarker-driven, and safe approaches for targeting CAFs, ultimately improving personalized treatment and outcomes for patients with NSCLC.